The Urban Sprawl Measurement In Egbeda Local Government Area, Ibadan - Adegboyega, Suleiman Abdul-Azeez (2015)
This study identified and examined the urbanized part of Egbeda Local Government Area of Oyo state and calculated the rate of expansion of the urban section, the spatial pattern of sprawl and dispersion of its land development (built-ups) with a view to determining rate of urban sprawl.